Notes on Some Plant Collections from Bachok and Several Forest Reserves in Kelantan. - Lim, A.L.; Haron, N.W.; Yong, K.T.; M.M., Wong (2010)
A botanical survey of Bachok and various forest reserves at Jeram Linang, Jeram Pasu and Bukit Bakar was part of an expedition from 14–20 June 2008 carried out by the IOES (Institute of Ocean and Earth Sciences) University of Malaya to survey and prepare an inventory of the biodiversity of the coastal region around Bachok, Kelantan. A total of 54 species from 30 families, consisting of seashore and mangrove plants were identified from the coastal area of Bachok and Semerak; while 89 species of flowering plants representing 44 families, a single gymnosperm, Agathis borneensis (Araucariaceae); and 15 genera and 23 species of mosses (from 10 families) were recorded in the three forest reserves. Several of the species collected were rarely found outside Kelantan.